The Integrated Talaqi Habituation Model in Improving the Quality of Students' Qur'anic Memorization in the Tahfidz Program ar SMP IT Oo Dompu - Eila Mawar Fitria; Maulana Maulana; Firmansyah Firmansyah; Fitrah Abu Bakar; Fajrul Al Islam; Ruslan Ruslan (Universitas Islam Sultan Agung, 2026)
This study aims to describe an integrated talaqi habituation model in improving the quality of students’ Qur’an memorization in the tahfidz program at SMP IT Oo Dompu. This research employed a qualitative approach with a descriptive design. The research subjects were students participating in the tahfidz program, while data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman.The results indicate that the integrated talaqi habituation model was implemented consistently through memorization submission and muroja’ah activities. This model effectively improved the quality of students’ Qur’an memorization, as reflected in accurate pronunciation, mastery of makharij al-huruf, proper application of tajwid rules, and increased fluency and consistency of memorization. Most students were able to achieve the predetermined memorization targets, and some exceeded the targets by continuing to the next juz. Therefore, the integrated talaqi habituation model can be considered a strategic approach for developing Qur’an memorization programs at the junior secondary school level.